PARADIGMA KONFLIK DALAM DRAMA ANALISIS UNSUR INTRINSIK, REKAYASA DRAMATIK, DAN RESOLUSI KONFLIK - Makaf, Akhyar (Institut Seni Indoensia Surakarta, 2018)
Conflict is an important element in dramas to assemble and unite intrinsic elements of theme, characterization, and groove. Conflict is also a determinant of the quality of a drama, because it is directly related to the reality of human life as individuals, as well as social beings. This study was conducted to determine the patterns, causes, effects, and conflict resolution presented in four realist dramas that differed from the time side of the incident, the background of the place, and the social setting, to find the resolution offered by the author, from the social conflicts that occurred in the community every period. The method used is analytic descriptive of conflict, intrinsic element, and social condition that underlies the creation of four realist dramas being sampled, Ketika Malam Bertambah Malam, Domba-domba Revolusi, Sayang Ada Orang Lain, and Pertja. In this study, it can be concluded while the conflict that arises is the depiction of social reality at the time this text is written, as well as the psychological condition of society in overcoming the problems that arise. Each author offers a reasonable and reasonable resolution of the conflict to provide a solution to each of the issues raised.Â Keywords :conflict, intrinsic, social, resolution.